Akurasi Arah Kiblat Kuburan Umum Songgen Desa Wanasaba Kabupaten Lombok Timur - Susanti, Chandra; Adawiyah, Siti Rabi'atul (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This research discusses two main points of discussion, namely the methods used by the community in Wanasaba Village in determining the Qibla direction of the Songgen public cemetery and the level of accuracy of the Qibla direction of the Songgen public cemetery in Wanasaba Village. The type of research used is field research with a qualitative descriptive approach. Data collection was obtained through direct observation in the field by carrying out measurements and structured interviews with resource persons. The results of this research show that the method used to determine the Qibla direction of the Songgen Public Cemetery is an estimation method by looking at the cardinal directions. The level of accuracy of the Songgen Public Cemetery after measurements were carried out using the Istiwa,aini method, it was found that the results ranged from 13° to 37°.